Grammatical Cohesion in Joe Biden’s Speech: An Analysis - Nurul Candra, Eva; Martiarini, Elyza; Reknosari, Reknosari (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
The aim of this research is to analyze the use of grammatical cohesion in Joe Biden’s victory speech as well as to find out the use of the most dominant type of grammatical cohesion in Jo Biden’s victory speech. The research method used is descriptive qualitative method. The data source was obtained from downloading a video in the form of a text transcript of Joe Biden’s victory speech, then identifying the use of grammatical cohesion. The types of grammatical cohesion which are the focus of this research are reference, substitution and conjunction. From the results of the analysis found the use of grammatical cohesion namely reference (174), substitution (22), Ellipsis (0) and conjunction (101). Thus, from this data, it can be concluded that in Joe Biden’s victory speech there was a lot of grammatical cohesion